Oral Tofacitinib and Systemic Corticosteroids, Alone or in Combination, in Patients With Moderate-to-Severe Alopecia Areata: A Retrospective Study - Zhang, Wenxin; Li, Xiangqian; Chen, Baifu; Zhang, Jianzhong; Torres-Culala, Kara Melissa T.; Zhou, Cheng (Frontiers in Medicine, 2022)
Introduction: Alopecia areata (AA) is an autoimmune hair loss mediated by CD8+ T cells. Treatment for moderate to severe AA is still challenging. JAK inhibitors (JAKi), such as tofacitinib, have been recently investigated as a promising treatment option for AA. Evidence on combination use of oral tofacitinib and systemic corticosteroids (SCs) for AA is still lacking. Objectives: To compare the efficacy and safety of monotherapy of oral tofacitinib and SCs, as well as their combination in patients with moderate to severe AA. Methods: Patients with moderate to severe AA, who have been treated with at least 3 months of monotherapy of tofacitinib or SCs, or in their combination, were included in this study. The efficacy and adverse events for these treatments were retrospectively analyzed. Results: Sixty-one patients with moderate to severe AA were included in the study. There were 12 (66.7%) of 18 patients in the SCs group, 12 (60.0%) of 20 patients in the tofacitinib group, and 18 (78.3%) of 23 patients achieved SALT50, with no significantly different among the 3 groups. Ratio of patients who achieved SALT50 was significantly higher in the patients with short duration of current hair loss episode (≤2 years) than those with duration of current hair loss episode (>2 years) in all three groups. There were 66.7% patients in SCs group, 35.0% patients in tofacitinib group, and 56.5% patients in combined group showed adverse effects (AE). Conclusion: Tofacitinib was an effective treatment for patients with moderate to severe AA and it was more tolerated than SCs. Combination of tofacitinib and SCs may have higher efficacy than SCs alone. Efficacy significantly decreased in patients with current episode of disease more than 2 years.